Возможности электронно-лучевой технологии получения композиционных материалов - Гречанюк, Н.И. (Электрические контакты и электроды, 2010)
Рассмотрены возможности процессов высокоскоростного испарения и последующей конденсации в вакууме металлов и неметаллов по созданию новых композиционных материалов: дисперсно-упрочненных, микрослойных, пористых. Приведены примеры их использования в промышленности. Розглянуто можливості процесів високошвидкісного випаровування і послідуючої конденсації в вакуумі металів та неметалів по створенню нових композиційних матеріалів: дисперсно-зміцнених, мікрошарових, пористих. Наведено приклади їх використання в промисловості. Among new materials obtained by evaporation and subsequent condensation in a vacuum, should include composite dispersion-hardened layered and porous materials. Dispersion-hardened condensates consist of a polycrystalline metal or ceramic matrix with uniformly distributed in the volume of dispersed particles of second phase. By varying the substrate temperature the deposition rate can change over a wide range average crystallite size from a few hundred microns to several hundred nanometers, the particles of strengthening phase from a few nanometers to several microns. Evaporation condensation technique allows to realize two typical approaches to the formation of structure microlayers condensates. 1. Produce condensation at relatively low temperatures and as a consequence of receiving condensates with a high density of crystal lattice within each layer. 2. Produce microslayers condensates with enough equilibrium structure at substrate temperatures of melting 0,4—0,5 least refractory layer. Electron-beam technology can be successfully used for porous materials. Examples of these composite materials are given.